Bootlegging : romanticism and copyright in the music industry - Marshall, Lee (Theory, culture & society (Unnumbered), 2005)
A valuable and distinctive contribution to the penumbra debate, refreshingly shedding light on some of the clichés of copyright, and alerting readers to the extra-legal factors that cannot be ignored in any socially-embedded study of copyright' - Stuart Hannabuss, Aberdeen Business School. 'Bootlegging is a smart, provocative and highly readable analysis of the high theory and low practices of music copyright and its transgressors. It is most refreshing to read a sociological analysis of a topic usually left to lawyers and industry apologists. An essential book for anyone who wants to understa.